Rapid and sensitive immunoassay for alpha-fetoprotein in serum by fabricating primary antibody–enzyme complexes using protein self-assembly. Issue 12 (8th March 2023) - Liu, Zilong; Liu, Xing; Pei, Hua; Bao, Kunlu; Su, Benchao; Cao, Hongmei; Wu, Long; Chen, Qi
Abstract : The focus of this manuscript is to develop a facile method for the uniform preparation of heptavalent PAECs and to investigate the performance of heptavalent PAECs in immunoassays. Abstract : Primary antibody–enzyme complexes (PAECs) are ideal immunosensing elements that simplify the immunoassay process and improve the uniformity of results due to their ability to both recognize antigens and catalyze substrates. However, the conventional fabrication methods of PAECs, such as direct gene fusion expression, chemical conjugation, enzymatic conjugation, etc., have low efficiency, poor reliability, and other defects, which limit the widespread application of PAECs. Therefore, we developed a convenient method for the fabrication of homogeneous multivalent PAECs using protein self-assembly and validated it using anti-alpha-fetoprotein nanobody (A1) and alkaline phosphatase (ALP) as models. Heptavalent PAECs showed a 4-fold enhancement in enzymatic catalytic activity compared to monovalent PAECs. Further, to verify the application of developed heptavalent PAECs in immunoassay, heptavalent PAECs were used as bifunctional probes to construct a double-antibody sandwich ELISA to detect AFP. The detection limit of the developed heptavalent PAEC-based ELISA is 0.69 ng mL −1, which is about 3 times higher than that of monovalent PAECs, and the whole detection process can be completed within 3 hours. In short, the proposed protein self-assembling method is a promising technology for developing high-performance heptavalent PACEs, which can simplify the detection process and improve detection sensitivity in various immunoassays.